Does tranexamic acid lead to changes in MRI-measures of brain tissue health in patients with spontaneous intracerebral haemorrhage? An MRI sub-study nested within the double-blind randomised controlled TICH-2 trial - Dineen, Robert A.; Pszczolkowski, Stefan; Flaherty, Katie; Law, Zhe Kang; Morgan, Paul S.; Roberts, Ian; Werring, David; Al-Shahi Salman, Rustam; England, Timothy J.; Bath, Philip M.W.; Sprigg, Nikola (BMJ Publishing Group Ltd, 2018)
Objectives: To test whether administration of the antifibrinolytic drug tranexamic acid (TXA) in patients with spontaneous intracerebral haemorrhage (SICH) leads to increased prevalence of diffusion-weighted MRI defined hyperintense ischaemic lesions (primary hypothesis) or reduced perihaematomal oedema volume, perihaematomal diffusion restriction and residual MRI-defined SICH-related tissue damage (secondary hypotheses). Design: MRI sub-study nested within the double-blind randomised controlled TICH-2 trial (ISRCTN93732214). Setting: International multi-centre hospital-based study. Participants: Eligible adults consented and randomised in the TICH-2 trial who were also able to undergo MRI scanning. To address the primary hypothesis a sample size of n=280 will allow detection of a 10% relative increase in prevalence of diffusion weighted imaging hyperintense lesions in the TXA group with 5% significance, 80% power and 5% imaging data rejection. Interventions: TICH-2 MRI sub-study participants will undergo MRI scanning using a standardised protocol at day ~5 and day ~90 after randomisation. Clinical assessments, randomisation to TXA or placebo and participant follow-up will be performed as per the TICH-2 trial protocol. Conclusion: The TICH-2 MRI sub-study will test whether TXA increases the incidence of new DWI-defined ischemic lesions or reduces perihaematomal oedema or final ICH lesion volume in the context of SICH.